2006
DOI: 10.1007/s10236-005-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Advanced insights into sources of vertical velocity in the ocean

Abstract: Estimating vertical velocity in the oceanic upper layers is a key issue for understanding ocean dynamics and the transport of biogeochemical elements. This paper aims to identify the physical sources of vertical velocity associated with sub-mesoscale dynamics (fronts, eddies) and mixed-layer depth (MLD) structures, using (a) an ocean adaptation of the generalized Q-vector form of the ω-equation deduced from a primitive equation system which takes into account the turbulent buoyancy and momentum fluxes and (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 23 publications
6
75
0
Order By: Relevance
“…Other processes-such as wind-induced frictional forces, diabatic processes, time-dependent near-and super-inertial motions, or higher-order corrections to the quasigeostrophic omega equation-could also generate vertical motion (Viú dez et al 1996;Giordani et al 2006;Nagai et al 2006;Thomas et al 2010). For example, a spatially uniform wind blowing over a current with lateral variations in vertical vorticity will generate Ekman pumping/suction owing to the modification of the Ekman transport by the vorticity (Stern 1965;Niiler 1969).…”
Section: February 2010 N O T E S a N D C O R R E S P O N D E N C Ementioning
confidence: 99%
“…Other processes-such as wind-induced frictional forces, diabatic processes, time-dependent near-and super-inertial motions, or higher-order corrections to the quasigeostrophic omega equation-could also generate vertical motion (Viú dez et al 1996;Giordani et al 2006;Nagai et al 2006;Thomas et al 2010). For example, a spatially uniform wind blowing over a current with lateral variations in vertical vorticity will generate Ekman pumping/suction owing to the modification of the Ekman transport by the vorticity (Stern 1965;Niiler 1969).…”
Section: February 2010 N O T E S a N D C O R R E S P O N D E N C Ementioning
confidence: 99%
“…The thermocline is diagnosed as the first level from the top of the ocean that experiences a density difference larger than 0.02 kg m −3 from the reference ocean level (5 m). This method has been applied successfully in the past by Paci et al (2005) and Giordani et al (2005Giordani et al ( , 2006 the POMME experiment datasets (Weill et al, 2003;Caniaux et al, 2005aCaniaux et al, , 2005bMémery et al, 2005).…”
Section: The One-dimensional Ocean Modelmentioning
confidence: 99%
“…In our study, MESO-NH is coupled to a one-dimensional ocean model (Gaspar et al, 1990) that has been shown to represent relatively well the vertical mixed layer structure and the SST evolution (Blanke and Delecluse, 1993;Alexander et al, 2000). Several ocean turbulence models are based on the Gaspar et al (1990) model equations (D'Alessio et al, 1998;Giordani et al, 2006). Using this air-sea coupled modelling system, the aim of the present article is to examine the ocean response to the high-resolution atmospheric forcing imposed during Mediterranean heavy precipitation events.…”
Section: Introductionmentioning
confidence: 99%
“…For Ro = 0.1, a typical value for mesoscale eddies, the nonlinear Ekman effect would be about 10 times as important for the windinduced vertical circulation as stress asymmetry from the air-sea velocity difference. Further, the nonlinear Ekman effect would be greatly enhanced in regions where the relative vorticity is locally intensified and is coupled with lateral density variations (3,6). High-resolution modeling studies show that the largest relative vorticity in eddying flows occurs in filament-like features along fronts and at the edges of eddies, rather than at eddy centers (4, 13), and routinely equals or exceeds the planetary vorticity in magnitude, bringing submesoscale effects into play.…”
mentioning
confidence: 99%